1992
DOI: 10.1177/000348949210100207
|View full text |Cite
|
Sign up to set email alerts
|

Voice Analysis of Patients with Endoscopically Treated Early Laryngeal Carcinoma

Abstract: Endoscopic laser resection of early (T1) laryngeal carcinoma has been advocated as an alternative to radiotherapy. Heretofore, the voice characteristics following this procedure have been addressed in only one review, which included patients treated by irradiation and laser resection. We present the first review of voice findings in 22 patients treated only by endoscopic laser resection of their vocal cord carcinomas. Laser resection of selected vocal cord carcinomas produced voice function results acceptable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

8
44
0

Year Published

1994
1994
2006
2006

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(52 citation statements)
references
References 9 publications
8
44
0
Order By: Relevance
“…There were not sufficient females in the study group to apply statistical tests, but a minor increase of 24.01 Hz in the fundamental frequency was seen compared to controls (202.23Hz). Similar results have also been reported by McGuirt et al (1992) 31 with a slightly higher average fundamental frequency compared to a normal control group. Voice tends to become more acute due to the removal of tissue and resulting compensation mechanisms.…”
Section: Discussionsupporting
confidence: 89%
“…There were not sufficient females in the study group to apply statistical tests, but a minor increase of 24.01 Hz in the fundamental frequency was seen compared to controls (202.23Hz). Similar results have also been reported by McGuirt et al (1992) 31 with a slightly higher average fundamental frequency compared to a normal control group. Voice tends to become more acute due to the removal of tissue and resulting compensation mechanisms.…”
Section: Discussionsupporting
confidence: 89%
“…It is not possible to discern whether differences between SLPs' and patients' ratings were a result of actual differences in perception of impairment or differences in each group's interpretation of the response categories. However, these findings correspond with conclusions drawn by Ellis and Fucci 7 and Beukelman and Yorkston, 15 who thought that SLPs would give speakers' intelligibility a higher rating than would untrained listeners based on level of training and practice, and McGuirt et al's 1992 study, 14 in which professionals gave a lower rating to patients' voice quality than did the patients themselves. The fact that strain was evaluated as worse by the patient is understandable, because this perceptual vocal attribute also has a physiologic component involving physical effort and resultant fatigue that is apparent to the patient but might not be apparent to other observers.…”
Section: Discussionsupporting
confidence: 83%
“…[4][5][6][7][8][9][10][11][12][13][14] Findings have indicated that intelligibility scores as well as perceptual strategies for judging voice quality can differ as a function of the level of training and practice the rater has. Speakers' intelligibility was rated as better by SLPs than by untrained listeners, 7,15 suggesting that SLPs might overestimate the general public's ability to comprehend impaired speakers as a result of their own experience with the patient population.…”
mentioning
confidence: 99%
“…Koufman 30 and McGuirt et al 31 found that voice quality after endoscopic excision was normal to mildly abnormal, but Fex and Fex 32 and Elner and Fex 33 showed that voice quality after endoscopic laser excision had permanently deteriorated. Other authors have also demonstrated poor voice quality after endoscopic laser treatment, 34,35 whereas Lehman et al 36 and Schuller et al 37 reported that their patients subjectively assessed their voices as near normal after radiotherapy.…”
Section: Discussionmentioning
confidence: 99%